Application of Time Token Learning Model in Speaking Skill of Grade VIII Students at Junior High School - Dilga, Fahra; Ulfah; Sukma; Juniati (Institut Agama Islam Negeri Palopo, 2025)
This study aims to describe the application of the Time Token learning model of students' speaking skills in Indonesian language subjects. The method used in this research is descriptive method with mixed research type of leatherative and quantitative. The research subjects were students of class VIII H SMP Negeri 9 Palu totaling 32 people, selected through simple random sampling technique. Data collection techniques used included observation, and documentation. The instruments used consisted of teacher and student activity observation sheets, as well as assessment of students' speaking skills through student learning outcomes data. The results showed that the teacher observation sheet was classified as very good, the student observation sheet also showed very effective results with a value of 91%, while the data on student learning outcomes in speaking skills reached 83 with a good category. These findings indicate that the application of the Time Token model is able to encourage equal distribution of speaking opportunities, increase student courage, and support active and structured speaking skills.